Penetration of SDF and AgF from the infected dentine towards the unaffected tooth structure - Mulder, Riaan; Potgieter, Nicoline; Noordien, Naeemah (Frontiers in Oral Health, 2023)
Background The use of SEM-EDS line scan analysis to evaluate the movement of ions from dental materials towards the tooth structure and the concept of ion movement is well established. This analysis technique was used to determine the ion movement of two commercially available silver- and fluoride-containing products. Methods This study aimed to compare the elemental analysis of primary molar teeth treated with silver diamine fluoride (SDF) and water-based silver fluoride (AgF) and to analyse the penetration of SDF and AgF from the infected dentine towards the healthy dentine. The teeth were cleaned from debris and contaminants off the roots and stored until use. A total of 15 primary molars with large active cavitated lesions, not extending into the pulp (specimens), were divided into three test groups: silver diamine fluoride (SDF) (n = 5), water-based silver fluoride (AgF) (n = 5), and deionised water (W) (n = 5) as the control group. The teeth were sectioned, embedded, and received SEM-EDS line scans. The line scan had a total length of 82.65 μm. The visible end of the infected dentine and the start of the more affected dentine were chosen as the starting point to ensure that the infected caries' line distribution towards the affected dentine's transition area was as standardized as possible. Therefore, the infected dentine length of the scan was 22.80 μm (8 scan points of 2.85 μm apart), and the affected dentine, including the healthy dentine, was 59.8 μm (21 scan points). The SEM-EDS line scan from each specimen determined the average fluoride, iodide, and silver weight percentage for that specimen. Results The 15 sample SEM-EDS line scans were used to determine the average ion movement in wt%. The Kruskall–Wallis test and Tukey's HSD test were completed at a p < 0.05. SDF and AgF presented no significant fluoride movement in terms of the weight percentage. There was, however, significantly more fluoride movement from infected caries to the healthy dentine with SDF and AgF (p = 0.0010053) compared to the control specimens treated with deionised water. There was no significant difference between SDF and AgF for the movement of the iodide (p = 0.5953) and silver (p = 0.3708) from infected caries to the healthy dentine. Conclusion SDF and AgF easily penetrated through infected caries and affected tooth structure to the healthy dentine for the line scan of 82.65 μm. There was no significant difference between SDF and AgF for the movement of ions within the infected dentine nor in the affected/healthy dentine.